Nanoparticles prepared by proso millet protein as novel curcumin delivery system. (1st February 2018) - Wang, Lei; Gulati, Paridhi; Santra, Dipak; Rose, Devin; Zhang, Yue
Highlights: Proso millet protein was extracted by either wet milling or aqueous ethanol. Curcumin loaded nanoparticles were prepared using millet protein and caseinate. Solubility and heat stability of curcumin were greatly improved by encapsulation. Encapsulation showed no impact on the antioxidant activities of curcumin. Ethanol-extracted protein showed better hydrophobicity and encapsulation behavior. Abstract: Encapsulation of lipophilic bioactive compounds using plant-derived proteins as delivery systems has received increasing interest. In this study, proso millet protein was extracted by either wet milling or 60% (v/v) aqueous ethanol and then used as the wall material to encapsulate curcumin. Millet protein was composed of prolamines that showed a significant difference in surface hydrophobicity depending on extraction procedure. The millet protein-curcumin nanoparticles were spherical with diameter around 250–350 nm. The entrapment efficiency ranged from 11.2% to 78.9%, with millet protein extracted by ethanol showing better performance than that by wet milling process. The encapsulated curcumin exhibited a lower degradation rate than free curcumin at 60 °C. The encapsulation showed no negative effect on the antioxidant activity of curcumin as assessed by the DPPH and ABTS assays. These results suggested that MP could be a promising encapsulant for the delivery of lipophilic compounds.